‘THE SCREAM OF THE MUTES:’ GENDER POLITICS AND TACTICAL INNOVATION IN BRAZILIAN RURAL MOVEMENTS - Peschanski, João Alexandre (Teoria & Pesquisa Revista de Ciência Política, 2020)
This paper investigates how internal dynamics contribute to the explanation of tactical innovations in social movements. As it is shown, shifts in repertoires of actions are associated with political conflicts within movements —which should be seen not as unitary actors but as unified collectives, in which internal negotiations play a key role in defining contentious politics. Gender dynamics within the Landless Workers’ Movement (MST) are investigated as an element to make sense of tactical and frame shifts in this social movement in the mid 2000s